Hypernetted chain calculations of molten uranium dioxide: Comparison of rigid ion potentials - Gunay, S. D.; Akdere, U.; Tasseven, C. (ELSEVIER, 2012)
The first liquid state calculations within the hypernetted chain approximation for molten uranium dioxide using six different rigid ion model potentials are presented and discussed. Applicability of the existing rigid ion potentials to the molten phase of uranium dioxide is examined. Despite the minor differences, the radial distribution functions and static structure factors of all potentials are typical of a system which melted from a fast ion conducting phase. Only in one case, the breakdown in the local structure of oxygen ions in the solid state is reflected in the calculated coordination numbers. The behavior of static dielectric function is related to the onset of freezing and found to mimic that of the classical one component plasma at low values of plasma parameter. Finally, the enthalpy change is calculated and compared with molecular dynamic simulation results and experimental data. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Uranium dioxide; Hypernetted chain theory; Static structure; Dielectric function; Enthalpy change; MOLECULAR-DYNAMICS SIMULATION; STATIC DIELECTRIC FUNCTION; INTERATOMIC POTENTIALS; UO2; Chemistry; Physics